Protection of chickens against fowl typhoid using field vaccine programs formulated with the live attenuated strain Salmonella Gallinarum ΔcobSΔcbiA - Penha, Rafael Antonio Casarin [UNESP]; Zancan, Fábio Tavares [UNESP]; Almeida, Adriana Maria De [UNESP]; Berchieri, Angelo [UNESP] (Instituto Biológico, 2018)
Salmonella enterica serovar Gallinarum biovar Gallinarum (SG) is a host-specific bacteria that causes the fowl typhoid (FT). This disease is highly pathogenic to commercial chickens, specially brown layers and breeders, causing acute septicemia followed by high morbidity and mortality. Vaccination is extensively adopted in the fields as a biosafety tool for prevention of isolated infections and outbreaks in commercial poultry flocks. The present study evaluated the use of an attenuated SG with deletions on genes cobS and cbiA (SGΔcobSΔcbiA) as a live vaccine, using vaccination schemes adjusted for field conditions. To this end, brown layers were used in two different experiments, to evaluate the long-term protection, necessary in the fields. The vaccination scheme on the first experiment consisted of two doses, the first at 4th week-of-age and the booster dose at 8th week-of-age with challenge at 16th week-of-age with wild SG strain. On the second experiment, the vaccination was carried out by different routes using three doses of the live vaccine, at 4th , 8th and 12th weeks-of-age, and the challenge was done at 20th weeks-of-age. After the challenge, the mortality was recorded during 28 days, and the egg production (experiment 2) was evaluated and compared with the group of unvaccinated layers. In both experiments, the mortality was significantly reduced, and the egg production was not affected in vaccinated layer-hens. In summary, this study shows the efficacy and the protection of different vaccination schemes against FT that can be applied under field conditions in commercial poultry farms.

Salmonella enterica sorovar Gallinarum biovar Gallinarum (SG) é uma bactéria hospedeira específica que causa o tifo aviário (TA). Essa doença é altamente patogênica em aves comerciais, especialmente galinhas poedeiras de linhagem vermelha e aves reprodutoras pesadas, causando septicemia aguda, e consequentemente, alta morbidade e mortalidade. A vacinação é amplamente utilizada no campo como uma ferramenta de biossegurança para a prevenção de infecções isoladas e surtos nas granjas avícolas comerciais. O atual estudo avaliou o potencial vacinal de uma cepa viva atenuada de SG com deleções nos genes cobS e cbiA (SGΔcobSΔcbiA), utilizando esquemas de vacinação formulados para utilização em campo. Para isso, as galinhas poedeiras de linhagem vermelha foram utilizadas em dois experimentos diferentes, para avaliar a proteção a longo prazo, necessária no campo. O esquema de vacinação no primeiro experimento consistiu em duas doses, a primeira na quarta semana de vida e a dose de reforço na oitava, e o desafio na 16ª semana com a estirpe selvagem SG. No segundo experimento, a vacinação foi realizada por diferentes rotas usando três doses da vacina viva, na quarta, na oitava e na décima segunda semana de vida, e o desafio foi feito na 20ª semana de vida. Após o desafio, a mortalidade foi acompanhada por 28 dias, e no experimento 2 a produção de ovos também foi avaliada e comparada com o grupo de galinhas não vacinadas. Em ambos os experimentos, a mortalidade foi significativamente reduzida, e a produção de ovos não foi afetada nos grupos de galinhas poedeiras vacinadas. Este estudo mostra a eficácia da proteção dos diferentes programas de vacinação contra o TA, que podem ser aplicados em granjas comerciais em condições de campo.
Proteção de aves contra o tifo aviário utilizando a cepa atenuada Salmonella Gallinarum ΔcobSΔcbiA em diferentes programas vacinais de campo
Keywords: immunity; attenuated; eggs; layer-hens; infection; imunidade; vacina viva atenuada; ovos; galinha; infecção